Impact of the COVID-19 pandemic on patients with liver cirrhosis—the experience of a tertiary center in Germany - Höner zu Siederdissen, Christoph; Schultalbers, Marie; Wübbolding, Maximilian; Lechte, Greta Sophie; Laser, Hans; Cornberg, Markus; Wedemeyer, Heiner; Maasoumy, Benjamin (Zeitschrift für Gastroenterologie, 2021)
Background The COVID-19 pandemic has caused a significant impact on the medical care of many diseases and has led to reduced presentations to the emergency department. Reduced presentations may be due to overwhelmed capacities of hospitals or collateral damage from fear of infection, lockdown regulations, or other reasons. The effect on patients with liver cirrhosis is not established.Objective We aim to assess the impact on the care of patients with liver cirrhosis in a tertiary center in Northern Germany.Methods All patients presenting to the emergency department with a diagnosis of cirrhosis between March 1 and May 31 from 2015–2020 were included. Reasons for presentation, duration of symptoms, the severity of liver disease, and 30-day mortality were assessed and compared between patients presenting during the COVID-19 pandemic and pre-COVID-19.Results Overall, 235 patients were included. Despite an overall decline in presentations to the emergency department by 11.7%, the frequency of patients presenting with liver cirrhosis has remained stable (non-significant increase by 19.5%). No significant difference could be detected for the MELD score, the CLIF-organ failure subscores, and the 30-day mortality before and during the COVID-19 pandemic. Up to 75% of patients with liver cirrhosis had symptoms >24 h before presenting to the emergency department.Conclusion Despite the overall trend of reduced emergency presentations during the COVID-19 pandemic, the frequency of presentations of patients with liver cirrhosis did not decline. Morbidity and mortality were not affected in a setting of disposable healthcare resources. The late presentation to the emergency department in many cirrhotic patients may open opportunities for interventions (i.e., with early telemedicine intervention).
Keywords: COVID; Zirrhose; Mortalität; Notfallversorgung